Profil Literasi Sains dalam Pembelajaran IPA di Era Covid-19: Studi Kasus di Universitas Terbuka - Mery Berlian; Iqbal Miftakhul Mujtahid; Rian Vebrianto; Musa Thahir (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Literacy skills are fundamental things that students must have in facing the industrial era 4.0 to be able to meet the needs of life in various situations. Scientific literacy is the ability to understand science, communicate science, and apply science skills to solve problems. However, the scores of Indonesian students on scientific literacy abilities are still far below the international standard scores set by the OECD institution. Seeing this phenomenon, this study aims to describe the profile of students' scientific literacy abilities. The research method used was a survey method. Informants who were used as research samples were 1210 Open University students. Data on students' scientific literacy abilities were collected through an online questionnaire using Google Form, then analyzed descriptively using the help of the SPSS program version 23.00 for Windows. The findings obtained in this study indicate the importance of scientific literacy skills that have a positive impact on knowledge, understanding and skills in using media, especially social media, which is currently often used as a source of information by audiences, especially students. Seeing the results of this study, the researcher recommended the need for universities or leaders so that students could improve students' scientific literacy skills.Keywords: ability, science literacy, natural science learning, covid-19 era, students.ABSTRAK Kemampuan literasi merupakan hal fundamental yang harus dimiliki oleh mahasiswa dalam menghadapi era industri 4.0 untuk dapat memenuhi kebutuhan hidup dalam berbagai situasi. Literasi sains merupakan kemampuan untuk memahami sains, mengkomunikasikan sains, serta menerapkan kemampuan sains untuk memecahkan masalah. Namun, skor siswa Indonesia pada kemampuan literasi sains masih jauh di bawah skor standar internasional yang ditetapkan oleh lembaga OECD. Melihat fenomena tersebut, penelitian ini bertujuan untuk mendeskripsikan profil kemampuan literasi sains mahasiswa. Metode penelitian digunakan adalah metode survey. Informan yang dijadikan sampel penelitian sebanyak 1210 orang mahasiswa Universitas Terbuka. Data kemampuan literasi sains mahasiswa dikumpulkan melalui kuisioner online menggunakan Google Form, kemudian dianalisis secara deskritif menggunakan bantuan Program SPSS versi 23.00 for Windows. Temuan yang diperoleh pada penelitian ini menunjukan pentingnya kemampuan literasi sains yang memberikan dampak positif bagi pengetahuan, pemahaman dan keterampilan dalam menggunakan media terutama media sosial yang saat ini sering dijadikan sumber informasi oleh khalayak terutama oleh kalangan mahasiswa. Melihat hasil penelitian tersebut, peneliti merekomendasikan perlunya universitas atau pimpinan agar mahasiswa dapat meningkatkan kemampuan literasi sains mahasiswa.Kata kunci: kemampuan, literasi sains, pembelajaran ipa, era covid-19, mahasiswa.